Non-vanishing of products of Fourier coefficients of modular forms of half-integral weight - Kohnen, Winfried (Abhandlungen aus dem Mathematischen Seminar der Universität Hamburg, 2018)
We prove a non-vanishing result in weight aspect for the product of two Fourier coefficients of a Hecke eigenform of half-integral weight.